Mentalizing in a movie for the assessment of social cognition (MASC): the validation in a taiwanese sample - Yu-Lien Huang; Tzu-Ting Chen; Isabel Dziobek; Huai-Hsuan Tseng (BMC Psychology, 2023)
Abstract Background The present study evaluated the psychometrics properties of a sensitive video-based test used in the evaluation of mentalizing skills, that is, the Movie for the Assessment of Social Cognition-Taiwanese version (MASC-TW). Methods We recruited two independent samples of nonclinical participants (N = 167) and adult patients with schizophrenia (N = 41). The MASC-TW and two other social cognition measures, namely the Chinese version of Theory of Mind task (ToM) and the Taiwanese version of the Diagnostic Analysis of Nonverbal Accuracy-2 (DANAV-TW-2), and an executive function measure of the Wisconsin Card Sorting Test (WCST), were administered to both groups. Results The MASC proved to be a reliable measure of mentalizing capacity, high Cronbach’s α value of 0.87. The intraclass correlation coefficient for the MASC-TW total correct scores was 0.85 across three waves of data collection. Across the entire sample, the scores on the MASC-TW were significantly correlated with verbal and nonverbal scores for the ToM task and recognition of facial and prosodic emotion on the DANAV-TW-2. Both executive function and emotion recognition emerged as noteworthy predictors of mentalizing, indicating that these two variables might play crucial roles in the development of mentalizing capacities. Finally, a receiver operating characteristic analysis revealed that in patients with schizophrenia, the MASC was the most accurate discriminator of diagnostic groups, highlighting the validity of the MASC. Conclusions Overall, the MASC-TW is an ecologically valid and useful tool for assessing mentalizing abilities in a Taiwanese population.